The Limits of HRD: Retrieving the Meaning of Workplace Learning - Junghwan Kim; K.P. Joo; K.P. Joo; Fred M. Schied (Adult Education Research Conference, 2010)
The purpose of this paper is to critically review the perspectives of HRD and its relationship to workplace learning by clarifying existing conceptual ambiguity and suggesting alternative approaches that incorporate various perspectives on work, workplace, and workplace learning